ENGLISH 4 ‘ONCE UPON A TIME’ IN DIGITAL AGE: : IMPACT OF DIGITAL STORYTELLING ON LISTENING SKILLS OF ESL LEARNERS - Hussain, Riaz; Khan, Muhammad Zeeshan; Asif, Muhammad (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
The revolutionized modes of presenting information have made this century the age of Information Technology. In today's world, technological advancements are being used in education. Different websites are offering their services for educational purposes. Several websites and software packages are being used for language teaching and language testing purposes. In this context, digital storytelling has the potential to increase the listening skills of ESL learners in Pakistan. Storytelling has always remained a vibrant part of different cultures. The art of storytelling is one of the ancient arts of human history and digital storytelling is the modern expression of this ancient art. A digital story can be based on anything that uses digital technology to describe a narrative. The present study tries to survey this dynamic tool of teaching language in the context of the 21st century’s social, cultural, and educational developments. The current study followed a mixed-method approach and employed both quantitative and qualitative techniques. The quasi experimental phase of the study was conducted to explore the effect of digital storytelling on the listening skills of ESL learners. 50 learners of BS class were taken as the sample for the present study. The quasi experimental phase of the study was based on a single group pre-test and post-test technique. The quantitative data was analyzed statistically through SPSS. In the results, the value sig. 0.000 shows that there was a significant improvement in the listening skills of the ESL learners. The current study finds that digital storytelling has a significant impact on the listening skills of ESL learners. The interviews with 15 ESL practitioners yielded insights about the responses and perceptions of the ESL teachers about digital storytelling. The ESL teachers who participated in the study were of the view that trainings on the use of digital storytelling should be imparted to the teachers